2013
DOI: 10.1088/0964-1726/22/11/115029
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and mechanical properties of the magnetorheological elastomer based on natural rubber/rosin glycerin hybrid matrix

Abstract: To improve the mechanical properties of the natural rubber based magnetorheological elastomers (MREs), rosin glycerin ester was added into the carrier matrix to enhance wettability and dispersibility of CI particles. Dynamic performance, including shear modulus, loss factor and viscosity of non-vulcanized matrix was measured by rheometer. In comparison to the natural rubber based MREs, the MR effect of these hybrid matrix MREs were higher and they can reach to 112% when the mass fraction of CI particles is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 33 publications
4
76
1
Order By: Relevance
“…The supplements that have been applied in MREs include zinc oxide and stearic acid as activators, sulfenamide (CZ) as an accelerator, sulfur as a crosslinking agent, and mercaptobenzothiazole. [49,97,117,[158][159][160][161][162][163][164][165][166][167][168] The concentration of each supplement influences the quality of the matrix; for example, excessive plasticizer will lead the rubber to become soft, and, hence, unable to sustain a load. [98] Synthetic rubber-based MREs received more attention than the natural rubber MREs since they have higher resistance to oil, better aging, and weathering as well as resilience over a wide temperature range.…”
Section: Matrix Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supplements that have been applied in MREs include zinc oxide and stearic acid as activators, sulfenamide (CZ) as an accelerator, sulfur as a crosslinking agent, and mercaptobenzothiazole. [49,97,117,[158][159][160][161][162][163][164][165][166][167][168] The concentration of each supplement influences the quality of the matrix; for example, excessive plasticizer will lead the rubber to become soft, and, hence, unable to sustain a load. [98] Synthetic rubber-based MREs received more attention than the natural rubber MREs since they have higher resistance to oil, better aging, and weathering as well as resilience over a wide temperature range.…”
Section: Matrix Elementsmentioning
confidence: 99%
“…In addition, an increment in the plasticizer content influences the magneto-induced modulus and MR effect. The latest work considering particle movement during the pre-structure process was conducted by Ge et al [159] A rosin glycerin ester was introduced to the natural rubber to synthesize the MRE, which had a high MR effect and low loss factor. Due to the occurrence of the rosin glycerin ester with good adherence property, the viscosity of the rubber compound declined, and, therefore, the attraction of the iron particles in the matrix during the magnetization process was easy.…”
Section: Manipulating Crosslink Densitymentioning
confidence: 99%
“…Having field-dependent modulus and damping properties, MREs have a broad range of possible applications such as vibration absorbers [2][3][4][5][6] sensing devices [7] and morphing structure [8]. The MR effect, which calculated from the storage modulus, is usually adopted to evaluate the MRE performance [9]. The hardness of the matrix has a significant influence on the MR effect [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lokander and Stenberg [8] have found that utilization of plasticizer in MREs enhanced the shear storage modulus. The introduction of plasticizer to the elastomeric materials be able to act as a lubricant and hence can raise the mobility of magnetic particles in the matrix and at the same time modify magnetic particles properties [9]. Therefore, in this study, sucrose acetate isobutyrate (SAIB) is utilized in the MREs preparation process to alter the viscosity of the ENR.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, it is well known that the compromise between mechanical properties and MR effects of existing MRE materials limits their engineering applications in which suitable quasi-static and dynamic mechanics performances are coordinately demanded. In order to develop high-performance MRE, many researchers and investigators improved formula, raw material selection, as well as manufacturing process (Hu et al, 2005;Böse, 2007;Chen et al, 2007;Li et al, 2008;Ge et al, 2013). However, a few academics have studied the approaches of altering exterior structure of MRE to improve the mechanical performance of MRE.…”
Section: Introductionmentioning
confidence: 99%